Evolution of the Theories of International Division of Labor: Methodological Aspects - Marinov, Velko (Research Papers, 2011)
This study has been dedicated to the analysis of historical development of the theories of international division of labor. The methodological aspects of the theories have been brought to the fore. Three basic stages in the development of the theories of international division of labor have been differentiated and respectively defined as a stage of the classical theory of comparative advantages, a stage of the neoclassical theory of factor proportions and a stage of the alternative theories of international division of labor.The analysis leads logically to the conclusion that the process of development of the theories of international division of labor combines elements of succession and of renovation. With a view to the fact that there is not a uniform (universal) theory of international division of labor, its modern structure can be explained adequately by constructing complex integrated models in which methodological principles, inherent in the various theoretical construct, find a place.The modern theories of international division of labor correspond to a broad range of other economic and social theories which reveals the multifaceted effects of the international division of labor in the conditions of economic globalization.